“A child’s nightmare. Mum comes and comforts her child.” Attachment evaluation as a guide in the assessment and treatment in a clinical case study - Salcuni, Silvia; Di Riso, Daniela; Lis, Adriana (Frontiers in Psychology, 2014)
There is a gap between proposed theoretical attachment theory frameworks, measures of attachment in the assessment phase and their relationship with changes in outcome after a psychodynamic oriented psychotherapy. Based on a clinical case study of a young woman with Panic Attack Disorder, this paper examined psychotherapy outcome findings comparing initial and post-treatment assessments, according to the mental functioning in S and M-axis of the Psychodynamic Diagnostic Manual (PDM). Treatment planning and post-treatment changes were described with the main aim to illustrate from a clinical point of view why a psycho-dynamic approach, with specific attention to an “attachment theory stance”, was considered the treatment of choice for this patient. The Symptom Check List 90 Revised (SCL-90-R) and the Shedler-Westen Assessment Procedure (SWAP–200) were administered to detect patient’s symptomatic perception and clinician’s diagnostic points of view, respectively; the Adult Attachment Interview (AAI) and the Adult Attachment Projective Picture System (AAP) were also administered as to pay attention to patient’s unconscious internal organization and changes in defense processes. A qualitative description of how the treatment unfolded was included. Findings highlight the important contribution of attachment theory in a 22-month psychodynamic psychotherapy framework, promoting resolution of patient’s symptoms and adjustment.